Prospects for conserving traditional poultry breeds of the Carpathian Basin - Szalay, István Tibor; Kisné Do thi , Dong Xuan; Virág, Györgyi; Szentes, Katalin Ágnes; Bódi, László (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
History of traditional Hungarian poultry, including several chicken, turkey, guinea-fowl, goose and duck breeds demonstrate their important role in agriculture and households of the Carpathian Basin. As the expansion of poultry industry made traditional breeds gradually disappear from the countryside, Hungarian preservation programmes with governmental subsidies, had to be started at the beginning of 1970’s to maintain original stocks of certain rare poultry breeds and varieties. Since 1997 conservation of traditional Hungarian poultry breeds has been managed and controlled by a non-governmental organisation (NGO): the Association of Hungarian Small Animal Breeders for Gene Conservation (MGE), which is at present the only officially registered breeding organization for all poultry genetic resources in the country. Conservation of local breeds of both field crops and farm animals, through the maintenance and development of different ecological types of production systems and products may have real importance in maintaining local agro-biodiversity and agro-ecosystems, which is the basis of sustainable agriculture. In this process, local poultry breeds should play a significant role, even in the near future. To achieve this goal, the first step should be the proper execution of the conservation programmes elaborated for local breeds. On the other hand, additional, new strategies to conserve traditional, local breeds are needed for multifunctional use of poultry genetic resources, including: the maintenance of functional in situ gene banks, research directed to the assessment of production, education at different levels, elaboration of sustainable production methods and marketable products, development of family poultry, making use of the capabilities of fancy breeders, completing field studies and surveys of local breeds in marginal regions and reintroduction of the breeds to villages, seeking for demonstration and popularization potentials, and adaptation of breeds in diverse environments. Some examples for the new prospects taken from the conservation experiences and practices are given in the paper.